ANÁLISIS DINÁMICO DE LA LÍNEA JURISPRUDENCIAL RESPECTO DE LA SUSTITUCIÓN DE LA CONSTITUCIÓN (2016)
The Constitution is founded on two main principles: democratic, typical of its sovereignty and popular exercise, and supremacy, why is positioned as superior law of these principles concurrent need to allow its reform and maintaining stability is derived, for avoid the stagnation of itself over time, just as weakness resulting flexibility is prevented in this dialectic found our theoretical analysis of constitutional law.The Colombian Constitutional Court has developed the doctrine of the impossibility of replacing the Constitution in the exercise of power reform, as this would be an excess in the competition who exercises that power, therefore, the Court could in these cases to exercise control constitutionality and declare unconstitutional the eventual reform. To verify as it has developed reconstruct the jurisprudential line and perform dynamic analysis.